Pengaruh Tingkat Disiplin Dan Kecerdasan Emosional Terhadap Kinerja Pegawai Pada Kantor Jasa Raharja Kota Kediri - Elsa Anastya; Anwar Bowo Leksono; Udik Jatmiko (Fakultas Ekonomi & Bisnis, Universitas Nusa Nipa, 2023)
For an agency or company, human resources are the main asset in every activity. Employees as human resources have great potential to achieve success in agency goals. The important role of human resources is that so that they can be used as effectively as possible, appropriate methods are needed to be able to move people or employees to work and use their abilities to the maximum. This goal can be achieved if the agency has good human resources and has high performance. This research aims to find out the influence of the level of discipline and emotional intelligence on employee performance at the Jasa Raharja Office, Kediri City. The analysis techniques used are validity test, reliability test, classical assumption test, multiple linear regression analysis, T test, F test. The population in this study was all 35 employees and the sample used was 32 respondents because it used a purposive sampling technique. The results of research at the Kediri City Jasa Raharja Office show that the variables discipline (X1) and emotional intelligence (X2) together influence the performance variable (Y). This can be proven from the results of the significance value of 0.000, where the significance value is smaller than 0.05.